2017
DOI: 10.1016/j.jns.2017.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic acid and its analogue can alter the opioid receptor G-protein signaling after acute treatment via NMDA receptor in rat cortex and striatum

Abstract: Previously, we have shown that the N-methyl d-aspartate (NMDA)-receptor antagonist kynurenic acid (KYNA) and its analogue KYNA1 do not bind directly to mu, kappa and delta opioid receptors in vitro. On the other hand, chronic administration of KYNA and KYNA1 resulted in region (cortex vs striatum) and opioid receptor-type specific alterations in G-protein activation of mouse brain homogenates. Here we describe for the first time the acute effect of KYNA and KYNA1 on opioid receptor function with the possible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…There are extensive data describing the interaction between the kynurenine and the endogenous opioid system [ 60 , 163 , 164 , 165 , 166 , 167 ]. It has also been demonstrated that KYNA and its analog KA1 can indirectly alter the G-protein signaling of opioid receptors through the NMDA receptor depending on the opioid receptor type (μ, κ or δ) and brain region (cortex or striatum) [ 168 , 169 ]. More importantly, the opioid, cannabinoid and the NMDA receptors are known to be co-localized and functionally interact with each other pair-wise in areas relevant to opioid dependence, tolerance and antinociception [ 84 , 142 , 170 , 171 , 172 , 173 , 174 , 175 ].…”
Section: Known and Potential Functional Interactions Betweenthe Enmentioning
confidence: 99%
“…There are extensive data describing the interaction between the kynurenine and the endogenous opioid system [ 60 , 163 , 164 , 165 , 166 , 167 ]. It has also been demonstrated that KYNA and its analog KA1 can indirectly alter the G-protein signaling of opioid receptors through the NMDA receptor depending on the opioid receptor type (μ, κ or δ) and brain region (cortex or striatum) [ 168 , 169 ]. More importantly, the opioid, cannabinoid and the NMDA receptors are known to be co-localized and functionally interact with each other pair-wise in areas relevant to opioid dependence, tolerance and antinociception [ 84 , 142 , 170 , 171 , 172 , 173 , 174 , 175 ].…”
Section: Known and Potential Functional Interactions Betweenthe Enmentioning
confidence: 99%
“…Furthermore, recent research has shed light on the mechanism of emotional learning, including its potential role in modulating affective motor function and emotional responses [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. The neural substrates involved in emotional learning, particularly KYNA, suggest a plausible impact on the limbic system, including structures such as the amygdala and prefrontal cortex, which are known to be involved in emotional regulation and associative learning [ 74 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. For example, it has been shown that KYNA and its synthetic analogs, such as SZR-72 and SZR-104, possess the ability not only to influence motor domains of behavior but also to potentially modulate emotional responses [ 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent research has shed light on the mechanism of emotional learning, including its potential role in modulating affective motor function and emotional responses [70][71][72][73][74][75][76][77]. The neural substrates involved in emotional learning, particularly KYNA, suggest a plausible impact on the limbic system, including structures such as the amygdala and prefrontal cortex, which are known to be involved in emotional regulation and associative learning [74,[78][79][80][81][82][83][84][85][86]. For example, it has been shown that KYNA and its synthetic analogs, such as SZR-72 and SZR-104, possess the ability not only to influence motor domains of behavior but also to potentially modulate emotional responses [87].…”
Section: Introductionmentioning
confidence: 99%